Letter (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0075-001 28th February, 1938. The Mayor's Secretary, Shoreditch Town Hall, Old Street, LONDON. E.C.1. Dr. and Mrs. H.B. Morgan thank the Mayor and Mayoress of Shoreditch for their kind invitation to a Reception in the Shoreditch Town Hall, on Friday March 11th, and have much pleasure in accepting the same. 292C/946/2/75